The influence of the Independent Teaching Platform (PMM) on Competence of History Teachers at State Senior High Schools in Palu City - Nuriyanti; Hasan; Idrus (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Education is an " effort" conscious and planned For realize atmosphere learning and fun learning so that participants educate in a way active develop potential himself For own religious spiritual power , control self , personality , intelligence , morals noble , and required skills​ Himself and Society. Research Problem Formulation Whether There is the influence of the Independent Teaching Platform (PMM) on Competence of History Teachers of Senior High Schools in Palu City . Research Objectives The Influence of the Independent Teaching Platform (PMM) on Competence of history teachers of state senior high schools in the city hammer . Benefits of research study This can enrich insight and knowledge Good in form theory or draft for researchers and readers , referring to the Merdeka Mengajar Platform in curriculum independent to teacher professionalism in the world of education. Research methods approach quantitative For research . Define method study quantitative as technique For investigate between connection variable use evaluate idea certain.for use technique statistics in numerical data analysis ,variables often measured use equipment . Research results Testing validity empirical done with using 36 respondents who were not is sample research . Respondents the originate from some teachers from schools located in the city Central Sulawesi hammer which has apply curriculum Independence.test validity This use formula correlation pearson product moment with level significant 5%. Research conclusion The discussion that has been described the can provide the conclusion that there is significant influence​ between Their Platforms Teach To Competence of History Teachers of State Senior High Schools in Palu City , Value its significance by 0.000 less from determination mark significance that has been established of 0.05 with mark contribution B 0.690 ( Hypothesis alternative accepted ). with the existence of PMM teachers feel helped in a way significance For increase professional teacher competence .